Effects of eight weeks of caffeine supplementation and endurance training on aerobic fitness and body composition - Malek, M. H.; Housh, T. J.; Coburn, J. W.; Beck, T. W.; Schmidt, R. J.; Housh, D. J.; Johnson, G. O. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to examine the effects of daily administration of a supplement that contained caffeine in conjunction with 8 weeks of aerobic training on VO2peak, time to running exhaustion at 90% VO2peak, body weight, and body composition. Thirty-six college students (14 men and 22 women; mean +/- SD, age 22.4 +/- 2.9 years) volunteered for this investigation and were randomized into either a placebo (n = 18) or supplement group (n = 18). The subjects ingested 1 dose (3 pills = 201 mg of caffeine) of the placebo or supplement per day during the study period. In addition, the subjects performed treadmill running for 45 minutes at 75% of the heart rate at O2peak, three times per week for 8 weeks. All subjects were tested pretraining and posttraining for O2peak, time to running exhaustion (TRE) at 90% [latin capital V with dot above]O2peak, body weight (BW), percentage body fat (%FAT), fat weight (FW), and fat-free weight (FFW). The results indicated that there were equivalent training-induced increases (p < 0.05) in O2 peak and TRE for the supplement and placebo groups, but no changes (p > 0.05) in BW, %FAT, FW, or FFW for either group. These findings indicated that chronic use of the caffeine-containing supplement in the present study, in conjunction with aerobic training, provided no ergogenic effects as measured by VO2peak and TRE, and the supplement was of no benefit for altering body weight or body composition.